Estudio de la cerámica de la costa norte de Santa Cruz: análisis iniciales de distribución y caracterización tecnomorfológica - Roumec, Antonella (2020)
More than 30 years ago, a systematic archaeological research began on the northern coast of Santa Cruz. Along this time, a large amount of ceramic sherdshave been recovered, which are uncommon in the Patagonic archaeological record in comparison to other materials, such as lithic artefacts or bone remains. Recently, in the context of the study of other aspects of the material life of hunter-gatherer populations of this area, we have begun to analyse the ceramic technology. Materials considered come from different contexts in superficial and stratigraphic position. In this paper, we present the first partial studies from the classification and analysis of all existing shreds in the collections of the research team. As a first step, a protocol and a descriptive database of the pieces were generated, where different types of variables were included. In this way 394 ceramics have been registered, mostly in certain archaeological localities of our study area, although its distribution covers the entire coastline of the research project area. Also, almost all sherds correspond to domestic ceramics, and there is a low percentage of pieces with different design elements. From this initial approach we have an extensive sample to carry out different kinds of studies in the future, such as morphological, decorative designs and analysis of residues, such as micro-nutrients, among others. We pretend to recover this part of the Patagonian archaeological heritage that remained forgotten.